Search for quasiparticle scattering in the quark-gluon plasma with jet splittings in pp and Pb-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Menzel, Marius; Nath, Abhishek; et al. (Physical review letters, 2025)
The ALICE Collaboration reports measurements of the large relative transverse momentum (𝑘𝑇) component of jet substructure in 𝑝⁢𝑝 and Pb-Pb collisions at center-of-mass energy per nucleon pair √𝑠NN=5.02 TeV. Enhancement in the yield of such large-𝑘T emissions in head-on Pb-Pb collisions is predicted to arise from partonic scattering with quasiparticles of the quark-gluon plasma. The analysis utilizes charged-particle jets reconstructed by the anti-𝑘T algorithm with resolution parameter 𝑅 =0.2 in the transverse-momentum interval 60<𝑝T,ch,jet<80 GeV/𝑐. The soft drop and dynamical grooming algorithms are used to identify high transverse momentum splittings in the jet shower. Comparison of measurements in Pb-Pb and 𝑝⁢𝑝 collisions shows medium-induced narrowing, corresponding to yield suppression of high-𝑘𝑇 splittings, in contrast to the expectation of yield enhancement due to quasiparticle scattering. The measurements are compared to theoretical model calculations incorporating jet modification due to jet-medium interactions (“jet quenching”), both with and without quasiparticle scattering effects. These measurements provide new insight into the underlying mechanisms and theoretical modeling of jet quenching.
Veröffentlicht: 16. Juli 2025
*ALICE Collaboration: S. Acharya, V. Anguelov, A. Berdnikova, L. Bergmann, A.G. Borquez Carcamo, M.C. Danisch, V.J.G. Feuillard, I. Fokin, P. Glässel, N.A. Grunwald, M.W. Menzel, A. Nath, Y. Pachmayer, K. Reygers, R. Schicker, F. Schlepper, J.J. Seo, G. Skorodumovs, J. Stachel, S.F. Stiefelmaier, C.A. van Veen, B. Windelband, A. Yuncu, F. Zanone, B. Zhang [und 1055 weitere Personen]
Gesehen am 07.01.2026